High‐mobility group box 1 released by autophagic cancer‐associated fibroblasts maintains the stemness of luminal breast cancer cells - Zhao, Xi‐Long; Lin, Yong; Jiang, Jun; Tang, Zhuo; Yang, Shuai; Lu, Lu; Liang, Yan; Liu, Xue; Tan, Jiao; Hu, Xu‐Gang; Niu, Qin; Fu, Wen‐Juan; et al. (The Journal of pathology, 2017)
Cancer stem cells/cancer‐initiating cells (CICs) and their microenvironmental niche play a vital role in malignant tumour recurrence and metastasis. Cancer‐associated fibroblasts (CAFs) are major components of the niche of breast cancer‐initiating cells (BCICs), and their interactions may profoundly affect breast cancer progression. Autophagy has been considered to be a critical process for CIC maintenance, but whether it is involved in the cross‐talk between CAFs and CICs to affect tumourigenesis and pathological significance has not been determined. In this study, we found that the presence of CAFs containing high levels of microtubule‐associated protein 1 light chain 3 (LC3II), a marker of autophagosomes, was associated with more aggressive luminal human breast cancer. CAFs in human luminal breast cancer tissues with high autophagy activity enriched BCICs with increased tumourigenicity. Mechanistically, autophagic CAFs released high‐mobility group box 1 (HMGB1), which activated its receptor, Toll‐like receptor (TLR) 4, expressed by luminal breast cancer cells, to enhance their stemness and tumourigenicity. Furthermore, immunohistochemistry of 180 luminal breast cancers revealed that high LC3II/TLR4 levels predicted an increased relapse rate and a poorer prognosis. Our findings demonstrate that autophagic CAFs play a critical role in promoting the progression of luminal breast cancer through an HMGB1–TLR4 axis, and that both autophagy in CAFs and TLR4 on breast cancer cells constitute potential therapeutic targets. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.